The effect of diet changes and food loss reduction in reducing the water footprint of an average American. Issue 6 (18th August 2018) - Mekonnen, Mesfin M.; Fulton, Julian
ABSTRACT: We analyzed the consumptive water reduction of diet shifting along with food waste reductions in the case of the United States. We find that a dietary shift to healthy diet will not always lead to reduced water footprint. Dietary shifts to vegan and vegetarian diets provide larger reduction in the consumptive water footprint. Reducing food loss and waste produced the largest potential water footprint reduction in our analysis of the US food system. Our findings suggest that a combination of measures that include dietary shift, reducing caloric intake, and reducing food waste result in a significant decline in water footprint.